2020
DOI: 10.3390/molecules25184282
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Tumor Microenvironment: Mechanistic Basis and Therapeutic Targets

Abstract: Resveratrol (3,4′,5 trihydroxystilbene) is a naturally occurring non-flavonoid polyphenol. It has various pharmacological effects including antioxidant, anti-diabetic, anti-inflammatory and anti-cancer. Many studies have given special attention to different aspects of resveratrol anti-cancer properties and proved its high efficiency in targeting multiple cancer hallmarks. Tumor microenvironment has a critical role in cancer development and progression. Tumor cells coordinate with a cast of normal cells to aid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 150 publications
0
31
0
1
Order By: Relevance
“…Moreover, though its activity on Nrf2, in another experimental context, a direct anti-inflammatory effect linked to a reduction in the levels and expressions of hepatic TNF-α, IL-1β, and IL-6 was highlighted [ 88 ]. Furthermore, resveratrol has been shown to elicit a remarkable anti-angiogenic effect during the development of DENA-induced hepatocellular carcinogenesis, blocking VEGF (vascular endothelial growth factor) expression through HIF-1α (hypoxia-inducible factor-1α) downregulation [ 89 ]. It has also been demonstrated that resveratrol is involved in the inhibition of cell cycle progression through reductions in the levels of p34cdc2 and cyclin B1 [ 90 ].…”
Section: Resveratrol and Liver Disease: Molecular Mechanismsmentioning
confidence: 99%
“…Moreover, though its activity on Nrf2, in another experimental context, a direct anti-inflammatory effect linked to a reduction in the levels and expressions of hepatic TNF-α, IL-1β, and IL-6 was highlighted [ 88 ]. Furthermore, resveratrol has been shown to elicit a remarkable anti-angiogenic effect during the development of DENA-induced hepatocellular carcinogenesis, blocking VEGF (vascular endothelial growth factor) expression through HIF-1α (hypoxia-inducible factor-1α) downregulation [ 89 ]. It has also been demonstrated that resveratrol is involved in the inhibition of cell cycle progression through reductions in the levels of p34cdc2 and cyclin B1 [ 90 ].…”
Section: Resveratrol and Liver Disease: Molecular Mechanismsmentioning
confidence: 99%
“…One of the main considerations about the treatment in the field of oncology is the evaluation of the toxic effects and risk of new therapies directed against cancers. Regarding melatonin, it has recently been stated that both physiological and pharmacological concentrations have no significant toxicity even at high doses, and aside from some rare exceptions [ 320 ], similar to other natural supplement like resveratrol [ 321 ].…”
Section: Melatonin Safety Profilementioning
confidence: 99%
“…In the past, resveratrol has been used for stomachache, hepatitis, arthritis, urinary tract infections, and inflammatory and cardiovascular diseases [50]. Recently, several studies have focused on the anticancer properties of resveratrol and revealed its high ability to target multiple cancer hallmarks [51]. Resveratrol has displayed apoptotic and antiproliferative effects on human cervical carcinoma cells by inhibiting cell growth, activating caspase-3 and caspase-9, upregulating of Bcl-2 associated X protein, and inducing expression of p53 [52].…”
Section: Resveratrolmentioning
confidence: 99%
“…The extraction efficiency of epigallocatechin gallate was improved by using electrochemical methods. It has been found that using polymeric electrode PAN/PPY enriched with nanoparticles of TiO₂ and rGO has saved time and increased efficiency to Recently, several studies have focused on the anticancer properties of resveratrol and revealed its high ability to target multiple cancer hallmarks [51]. Resveratrol has displayed apoptotic and antiproliferative effects on human cervical carcinoma cells by inhibiting cell growth, activating caspase-3 and caspase-9, upregulating of Bcl-2 associated X protein, and inducing expression of p53 [52].…”
Section: Egcg (Epigallocatechin Gallate)mentioning
confidence: 99%